Population Diversity of Antibiotic Resistant Enterobacterales in Samples From Wildlife Origin in Senegal: Identification of a Multidrug Resistance Transposon Carrying blaCTX–M–15 in Escherichia coli - Abdallah, Rim; Kuete Yimagou, Edmond; Hadjadj, Linda; Mediannikov, Oleg; Ibrahim, Ahmad; Davoust, Bernard; Barciela, Amanda; Hernandez-Aguilar, R. Adriana; Diatta, Georges; Sokhna, Cheikh; Raoult, Didier; Rolain, Jean-Marc; et al. (Frontiers in Microbiology, 2022)
Introduction: The role of wildlife in the transmission of AMR is suspected but scarcely reported in current studies. Therefore, we studied the dynamics and prevalence of antibiotic-resistant Enterobacterales in antibiotic-limited areas of Senegal. Materials and methods: We collected fecal samples from monkeys and apes (N= 226) and non-fecal samples (N= 113) from Senegal in 2015 and 2019. We grew the samples on selective media, subsequently isolated AMR Enterobacterales, and then sequenced their genomes. Results: We isolated 72 different Enterobacterales among which we obtained a resistance rate of 63% for colistin (N=47/72) and 29% for third-generation-cephalosporin (C3G) (29%, N= 21/72). Interestingly, almost 46% of our isolates, among Enterobacter sp., Citrobacter cronae and Klebsiella aerogenes, belong to 34 new STs. Moreover, the genes blaCTX-M-15, blaTEM1B, sul2, dfrA14, qnrs, aph(3''), aph(6), tetA and tetR harboured within a transposon on the IncY plasmid of ST224 E. coli were transferred and inserted into a ST10 E. coli phage coding region. Conclusion: Wildlife constitutes a rich, unexplored reservoir of natural microbial diversity, AMR genes and international resistant clones pathogenic in humans. The presence of a transposon that carries AMR genes is intriguing since no antibiotics are used in the non-human primates we studied.